Mentoring teacher trainees in times of COVID-19: reflection on practice. Issue 2 (3rd July 2021) - Howard, C.
ABTRACT: The pandemic of Coronavirus in 2020–21 (COVID-19) has impacted upon the lives of many university-based school mentors and teacher trainees. The strong commitment and partnership between mentors, trainees and training settings has, despite such challenges, allowed teacher training to continue and flourish. This has been achieved through relentless innovation and change so that schools, mentors, course leaders and training institutions can continue to support their trainees. Using virtual support for trainees in schools, coupled with a strong school training partnership which is staffed by committed mentors this has meant that trainees continue to progress towards their goal of achieving qualified teacher status. Personal relationships between mentors and trainees have underpinned trainees' emotional, personal and professional wellbeing. This reflective paper, written by a university-based teacher training mentor, outlines how change has been managed, and the factors that have secured success in these most turbulent of times.